Proses Belajar-Mengajar di Perguruan Tinggi Berwawasan Pencipta Kerja - Suyanto Suyanto (Jurnal Ilmu Pendidikan, 2016)
Recently, the unemployment of college graduates has been greater and greater. Even more, in the recent economic crisis, college graduates face heavy challenges in entering the work place. They have to compete to find out employment which is more and more abundant due to the sharp decrease of our economic investment. Our college graduates at present, and even more in the beginning of the 21st century, will also face neck to neck global competition in finding jobs. Therefore, our colleges have to set up a new orientation in conducting teaching-learning processes so that they are able to be responsible to their stakeholders. Our colleges need to renew their vision, mission, and commitment in carrying out the teaching-learning processes to be able to produce graduates with the vision of job creators